Perbedaan Hasil Belajar Kognitif Peserta Didik Dalam Pemanfaatan Media Pembelajaran Wordwall Pada Materi Hidrosfer Di Kelas X SMAN 17 Jakarta - Marsyandha, Lady; Sya, Ahman; Hardi, O.S. (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze the differences in students' cognitive learning outcomes in the use of Wordwall learning media on the Hydrosphere Material in Class X SMAN 17 Jakarta This study used a quasi-experimental study with a Nonequivalent Control Group Design research design. The sampling technique was purposive sampling with samples from the experimental class X-D and the control class X-C. The experimental class was treated with Wordwall media while the control class was given treatment with Powerpoint media. Data analysis techniques used validity and reliability tests on the Pre-test and Post-test instruments, analysis prerequisite tests, and hypothesis testing. Based on the research results, the Pre-test value for the experimental class was obtained with an average value of 40.00 while the control class was 39.66. In the Post-test the experimental class has an average value of 65.48 while the control class is 52.41. Test data analysis using the Independent Sample t-test on the basis of the provisions of the Significance Level (α) of 0.05 or 5%. The results of the hypothesis test obtained a sig value of 0.001. So the sig value is 0.001 <0.05. It can be concluded that the results of the hypothesis test H0 are rejected and Ha is accepted, meaning that there are differences in the cognitive learning outcomes of students using Wordwall learning media and without using Wordwall learning media on the hydrosphere material in class X SMAN 17 Jakarta.